2004
DOI: 10.1055/s-2004-829632
|View full text |Cite
|
Sign up to set email alerts
|

Greek Version of the Epworth Sleepiness Scale

Abstract: Our data validate the ESS for application in Greek-speaking populations. Despite relevant influences of language and cultural background, ESSgr is a valuable tool for clinical management and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
1
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 8 publications
7
72
1
8
Order By: Relevance
“…For the 135 individuals assessed in the present study, the scores obtained on the ESS-BR showed internal consistency similar to that of translations validated elsewhere, (24)(25)(26)(27)(28) despite the cultural and language differences among the populations analyzed. Comparing the ESS-BR scores obtained in the present study with those obtained in studies applying the original ESS, we found the scores to be similar for the control and OSAHS groups.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…For the 135 individuals assessed in the present study, the scores obtained on the ESS-BR showed internal consistency similar to that of translations validated elsewhere, (24)(25)(26)(27)(28) despite the cultural and language differences among the populations analyzed. Comparing the ESS-BR scores obtained in the present study with those obtained in studies applying the original ESS, we found the scores to be similar for the control and OSAHS groups.…”
Section: Discussionsupporting
confidence: 77%
“…(25)(26)(27)(28) In one study, (19) the ESS scores were significantly higher for patients with severe OSAHS than for those with mild or moderate OSAHS (p < 0.001), although no statistically significant difference was found between the mild and moderate forms. Unlike other validation studies, the present study evaluated only individuals submitted to polysomnography, which enhanced the stringency of the selection of the groups.…”
Section: Discussionmentioning
confidence: 93%
“…Subjective sleepiness and CPAP treatment response A subjective tendency for sleepiness was evaluated by means of the validated Greek version [18] of the ESS [19], on initial assessment and at a follow-up assessment o6 months later. Higher ESS scores indicate a greater subjective tendency for daytime sleepiness.…”
Section: Apparatus and Cpap Compliancementioning
confidence: 99%
“…Diabetes was defined by a fasting glycaemia above 126 mg/dl [18] and impaired fasting glucose (IFG) as fasting glucose levels ≥110 mg/dl. Sleepiness was evaluated by the Greek version of the Epworth Sleepiness Scale [19]. …”
Section: Methodsmentioning
confidence: 99%